Radiators in Hydronic Heating Installations Structure, Selection and Thermal Characteristics - Muniak, Damian Piotr; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses key design and computational issues related to radiators in hydronic heating installations. A historical outline is included to highlight the evolution of radiators and heating technologies. Further, the book includes a chapter on thermal comfort, which is the decisive factor in selecting the ideal heating system and radiator type. The majority of the book is devoted to an extensive discussion of the types and kinds of radiators currently in use, and to identifying the reasons for the remarkable diversity of design solutions. The differences between the solutions are also addressed, both in terms of the effects of operation and of the thermal comfort that needs to be ensured. The book then compares the advantages and disadvantages of each solution, as well as its potential applications. A detailed discussion, supported by an extensive theoretical and mathematical analysis, is presented of the computational relations that are used in selecting the radiator type. The dynamics of radiator heat output regulation are also covered, with particular emphasis on underfloor-surface radiators, for which this aspect is particularly important. The book closes with a chapter presenting computational examples. It includes numerous examples of calculations for all essential thermal parameters of radiator operation in heating installations.
Thermal comfort -- Radiators in hydronic heating installations Historical outline, types and structure -- Radiator thermal characteristic -- Methods of the radiator heat output control -- The sizing of surface radiators -- Selection of radiators for heating installations.
Keywords: Engineering design; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Computational intelligence; Buildings -- Environmental engineering; Engineering Design; Engineering Thermodynamics, Heat and Mass Transfer; Computational Intelligence; Building Physics, HVAC